2017
DOI: 10.1038/ncomms14246
|View full text |Cite
|
Sign up to set email alerts
|

A non-canonical mismatch repair pathway in prokaryotes

Abstract: Mismatch repair (MMR) is a near ubiquitous pathway, essential for the maintenance of genome stability. Members of the MutS and MutL protein families perform key steps in mismatch correction. Despite the major importance of this repair pathway, MutS–MutL are absent in almost all Actinobacteria and many Archaea. However, these organisms exhibit rates and spectra of spontaneous mutations similar to MMR-bearing species, suggesting the existence of an alternative to the canonical MutS–MutL-based MMR. Here we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
133
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(143 citation statements)
references
References 51 publications
9
133
1
Order By: Relevance
“…Gaiella occulta genome sequence has the key enzymes for the main DNA repair mechanisms, except for the mismatch repair pathway. Genes mutS and mutL were not encountered, as in many Actinobacteria and Archaea (Castañeda‐García et al, ). A gene coding for the endonuclease NucS (Gocc_1770) was identified, suggesting G. occulta may use the noncanonical mismatch repair pathway described recently for Mycobacterium smegmatis and Streptomyces coelicolor (Castañeda‐García et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaiella occulta genome sequence has the key enzymes for the main DNA repair mechanisms, except for the mismatch repair pathway. Genes mutS and mutL were not encountered, as in many Actinobacteria and Archaea (Castañeda‐García et al, ). A gene coding for the endonuclease NucS (Gocc_1770) was identified, suggesting G. occulta may use the noncanonical mismatch repair pathway described recently for Mycobacterium smegmatis and Streptomyces coelicolor (Castañeda‐García et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Genes mutS and mutL were not encountered, as in many Actinobacteria and Archaea (Castañeda‐García et al, ). A gene coding for the endonuclease NucS (Gocc_1770) was identified, suggesting G. occulta may use the noncanonical mismatch repair pathway described recently for Mycobacterium smegmatis and Streptomyces coelicolor (Castañeda‐García et al, ). Thermoleophilum album and S. soli may also use this alternative mismatch repair pathway as they also lack homologs of mutS and mutL and have a nucS homolog.…”
Section: Resultsmentioning
confidence: 99%
“…The homologues of MutS exist in all prokaryotes, with the exception of Actinobacteria, Mollicutes and part of the Archaea [11]. Bacteria of the Actinobacteria Phylum and Archaea encode a non-canonical MMR system (NucS/endoMS) [12]. For Mollicutes, it was reported that the histone-like protein HU (Hup2) in M. gallisepticum might play it role in mismatch repair [13].…”
Section: Introductionmentioning
confidence: 99%
“…Mycobacterial DNA repair is an under‐explored area, mostly understood in terms of homology . However, recent studies in the field of DNA repair have revealed the presence of several novel proteins and pathways in mycobacteria . A previous analysis of the mycobacterial genomes, in our laboratory, revealed the presence of a protein RecG wed , with a standalone wedge domain .…”
Section: Introductionmentioning
confidence: 91%